Assessment of knowledge of evidence‐based maternal and newborn care practices among midwives and nurses in six provinces in Indonesia. (27th February 2019) - Sethi, Reena; Tholandi, Maya; Amelia, Dwirani; Pedrana, Alisa; Ahmed, Saifuddin
Abstract: Objective: To investigate knowledge of obstetric and newborn care guidelines among midwives and nurses in Indonesia, whether knowledge differs between health centers ( puskesmas ) and hospitals, and factors associated with knowledge. Methods: Cross‐sectional knowledge assessments of 409 health workers in 56 public and private health facilities across six provinces were conducted. Poisson regression models examined relationships between knowledge; health workers' age; in‐service education about labor, delivery, or newborn care in the past 3 years; and supervision in the past 3 months. Results: The mean maternal care score among the 302 midwives for the 10 questions was 3.3 (standard deviation [SD]1.8). Hospital midwives performed slightly better than puskesmas midwives: 3.8 correct (confidence interval [CI], 3.43–4.19) vs 3.0 correct (CI, 2.77–3.26), which was a statistically significant difference. The mean knowledge score for three newborn care questions was 0.79 (SD 0.87). There was no statistically significant difference in scores between hospital workers and puskesmas providers (0.80 correct [CI, 0.64–1.00] vs 0.78 correct [CI, 0.67–0.92]). Receipt of supervision was not associated with maternal or newborn health knowledge scores. Conclusions: There is a need to improve knowledge of maternal and newborn care guidelines among midwives and nurses in Indonesia. Abstract : Cross‐sectional knowledge assessments of nurses and midwives in health facilities in Indonesia identified knowledge gaps related to maternal and immediate newborn care clinical guidelines.